Charting the territory: Describing the functional abilities of children with progressive neurological conditions. (December 2017) - Tatla, Sandy K.; Holsti, Liisa; Andrews, Gail Stephanie; Feichtinger, Leanne; Steele, Rose; Siden, Harold
Highlights: The PEDI is a feasible measure of functioning in children with PNCs. Children with PNCs demonstrated stable functional abilities over 2 years. In children with PNC, age did not significantly affect functional skills. Children with PNC required increased mobility modifications over a 2-year period. Caregiver assistance was greatest in self-care tasks compared to mobility and social function. Abstract: Aims: Little is known about the functional abilities of children with progressive genetic, metabolic, or neurological conditions (PNCs). In this study, children with PNCs were followed over a 2-year period to assess their functional abilities over time. Specific aims were to: 1) describe the changes in functional skills and the effects of age for children with PNCs, 2) assess changes in these children's need for caregiver assistance over time, and 3) examine relationships between these children's functional skills and need for caregiver assistance. Methods: This study involved a longitudinal, descriptive design with three assessments occurring at Baseline, Year 1, Year 2. Functional skills and caregiver assistance were assessed by the Pediatric Evaluation of Disability Inventory (PEDI). The PEDI questionnaire was completed at baseline and then yearly by parents, along with the assistance of a trained research assistant (RA). Results: The study was completed with 83 children (mean age at Baseline = 7.1yrs, SD = 4.6). Mean Functional skills scores were in the low ranges at Baseline and did not change significantly across time points (F(2, 71) = 0.437, p = 0.58). Time point had no effect on caregiver assistance ratings (p < 0.2); however, children required greater amounts of help with self-care at later time points than for other functional domains. Statistically significant correlations were found between PEDI-Functional skills and caregiver assistance ratings (r = 0.80-0.90, p < 0.01). Conclusions: Functional skills were low for these children overall, irrespective of age. In children with PNCs: 1) mean functional skills did not change significantly over time; 2) caregiver assistance scores remained stable and 3) functional skills and levels of caregiver assistance were strongly positively correlated. Further research to explore the long-term functional trajectory in children with a PNC is recommended.